Composition and Density of Marine Debris in the Mangrove Ecosystems of the Sungai Rawa Village, Sungai Apit Subsdistrict, Siak Regency, Riau Province - Fajriah, Nurul; Fauzi, Muhammad; Sumiarsih, Eni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2019)
Marine debris is a type of pollutant that commonly found in the mangrove ecosystems. A research aims to determine the composition and density of marine debris in the mangrove ecosystem of the Sungai Rawa Village was conducted in June - July 2018. A survey method was used in this study. Samplings were done three times (once / 2 weeks) at 3 stations namely S1 (ecotourism area), S2 (natural mangrove forest) and S3 (port area and settlement area). Marine debris were collected from 3 plots (10 x 10 m) placed along the transect line. The type of marine debris found in the mangrove ecosystem consists of plastic, glass, rubber, fabric, styrofoam, nets, cans, wood, steel and paper. The density of marine debris based on its characteristics are: megadebris (0.01 - 0.04 items/m2; 4.61 - 34.67 grams/m2), macrodebris (1.43 - 4.75 items/m2; 249.19 - 724.53 grams/m2), mesodebris (0.79 - 2.20 items/m2; 1.54 - 3.23 grams/m2). The most common marine debris found is plastic (69.27 %) and styrofoam (15.65 %).